Effect of damage on the dynamic characteristics of St. Nicholas cathedral in Cyprus - Votsis, Renos; Kyriakides, Nicholas; Tantele, Elia; Chrysostomou, Christis (My University, 2015)
The protection of monuments from aging and natural hazards, such as earthquakes, is very important since such structures are part of the cultural heritage of many countries around the world. In order to protect them from earthquakes, their structural system has to be identified and their capacity to withstand dynamic loads has to be clearly understood. Due to the large size of such structures and the limitations imposed by antiquities departments on the methods that can be used to obtain the properties of the materials of these structures and their dynamic characteristics, the ambient vibration survey method seems to be the most appropriate one to be used. Once the dynamic characteristics are identified, they will form a bench mark and any deviation in these parameters will be used for the identification and localization of damage caused to the structure, either due to environmental factors and aging, or due to an earthquake. In this work the dynamic characteristics of St. Nicholas Cathedral obtained through ambient vibration survey and the subsequent calibrated FE model are presented. Then a numerical sensitivity analysis is performed, in which damage is inflicted at vulnerable sections of the structure and the effects of this damage on the dynamic characteristics of the structure are recorded. Finally, conclusions are drawn on the type of sensors and locations they should be placed, as well as on the effectiveness of a monitoring system in identifying and localizing damage on the structure.
Keywords: Damage assessment; Dynamic characteristics; Finite element modelling; Masonry monument